Memories of Entanglement: Conflicts Around Sexuality at the Sydney Women's Commission 1973. Issue 111 (2nd January 2022) - Torzillo, Emma; Goodall, Heather
ABSTRACT: The Women's Commission held in Sydney in March 1973, was organised by Women's Liberation as a 'speak out', allowing the theories and practices of the new wave women's movement to be shared and contested. This paper investigates tensions around lesbianism and feminism by considering both archival evidence from 1973 of the Commission's 'Women as Sex Objects' session and oral histories undertaken in 2003 with five participants, each at some stage identifying as lesbian. Both archives and the later reflective interviews have been revisited recently in the light of feminist and queer theory. The paper identifies three themes in Commission tensions: emotions, including entangled relationships, as motivations; changing views on gender fluidity; and marginalisation. Both archive and oral history are needed to allow a deeper understanding of each theme, all three of which continue to shape the women's movement.